Cell Adhesion and Matrix Stiffness: Coordinating Cancer Cell Invasion and Metastasis - Gkretsi, Vasiliki; Stylianopoulos, Triantafyllos (Frontiers in Oncology, 2018)
Metastasis is a multistep process in which tumor extracellular matrix (ECM) and cancer cell cytoskeleton interactions are pivotal. ECM is connected, through integrins, to the cell’s adhesome at cell-ECM adhesion sites and through them to the actin cytoskeleton and various downstream signaling pathways that enable the cell to respond to external stimuli in a coordinated manner. Cues from cell-adhesion proteins are fundamental for defining the invasive potential of cancer cells, and many of these proteins have been proposed as potent targets for inhibiting cancer cell invasion and thus, metastasis. In addition, ECM accumulation is quite frequent within the tumor microenvironment leading in many cases to an intense fibrotic response known as desmoplasia and to stiffening of the tumor. Stiffening is not only required for a tumor to be able to displace the host tissue and grow in size but also contributes to cell-ECM interactions and can promote cancer cell invasion to surrounding tissues. Here we review the role of cell adhesion and matrix stiffness to cancer cell invasion and metastasis.